2022
DOI: 10.1021/acsnano.1c10705
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer Coupling of a Two-Dimensional Kondo Lattice with a Ferromagnetic Surface in the Antiferromagnet CeCo2P2

Abstract: The f-driven temperature scales at the surfaces of strongly correlated materials have increasingly come into the focus of research efforts. Here, we unveil the emergence of a two-dimensional Ce Kondo lattice, which couples ferromagnetically to the ordered Co lattice below the P-terminated surface of the antiferromagnet CeCo 2 P 2 . In its bulk, Ce is passive and behaves tetravalently. However, because of symmetry breaking and an effective magnetic field caused by an uncompensated ferromagnetic Co layer, the Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Our electronic structure calculations (Fig. 1 d) as well as recent ARPES data 28 give no indication of flat bands in the bulk of CeCo 2 P 2 . The very low Sommerfeld coefficient found in specific heat measurements 28 further excludes the presence of heavy quasiparticles close to E F .…”
Section: Resultsmentioning
confidence: 37%
See 4 more Smart Citations
“…Our electronic structure calculations (Fig. 1 d) as well as recent ARPES data 28 give no indication of flat bands in the bulk of CeCo 2 P 2 . The very low Sommerfeld coefficient found in specific heat measurements 28 further excludes the presence of heavy quasiparticles close to E F .…”
Section: Resultsmentioning
confidence: 37%
“…We found that the intermetallic system CeCo 2 P 2 28 is a rare exception from this general behaviour. In CeCo 2 P 2 , the Co moments have a stacked antiferromagnetic (AFM) order along the c axis with each layer being ferromagnetically (FM) ordered along c below T N ≈ 440 K 30 .…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations